2021
DOI: 10.3389/fmolb.2021.748449
|View full text |Cite
|
Sign up to set email alerts
|

Role of BET Proteins in Inflammation and CNS Diseases

Abstract: Bromodomain and extra-terminal domain (BET) proteins consist of four mammalian members (BRD2, BRD3, BRD4, and BRDT), which play a pivotal role in the transcriptional regulation of the inflammatory response. Dysregulated inflammation is a key pathological process in various CNS disorders through multiple mechanisms, including NF-κB and Nrf2 pathways, two well-known master regulators of inflammation. A better mechanistic understanding of the BET proteins’ role in regulating the inflammatory process is of great s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 85 publications
(153 reference statements)
0
19
0
Order By: Relevance
“…To date, recognition for the roles of BRD4 in neurological conditions is limited [ 5 ]. Because PROTAC molecule dBET1 contains a BET bromodomain binding moiety JQ1 with much higher selectivity and affinity for BRD4 than other BET members, BRD4 functional regulation is the primary effect of dBET1 [ 5 , 42 44 ]. PROTAC technique is a leading strategy for targeting protein degradation through the ubiquitin proteosome system.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, recognition for the roles of BRD4 in neurological conditions is limited [ 5 ]. Because PROTAC molecule dBET1 contains a BET bromodomain binding moiety JQ1 with much higher selectivity and affinity for BRD4 than other BET members, BRD4 functional regulation is the primary effect of dBET1 [ 5 , 42 44 ]. PROTAC technique is a leading strategy for targeting protein degradation through the ubiquitin proteosome system.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence shows that several pro-inflammatory cytokines, such as IL-1β, IL-6, and TNF-α, as well as other potential cytotoxic molecules, are released in response to ischemic insults [ 46 ]. Previous reports showed that JQ1-treated animals exhibit a marked reduction in the expression of pro-inflammatory mediators IL-1β, IL-6, IL-17, IL-18, and TNF-α in the brain in rodent ischemic stroke models [ 5 , 47 ]. Emerging evidence suggests that BRD4 may act as a critical transcriptional regulator of NF-κB-dependent inflammatory gene expression, such as CCL2, CXCL1, and CXCL10 [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations